Lifestyle modifications and complementary treatments for hidradenitis suppurativa. Issue 3 (28th January 2022) - De, Devea R.; Rick, Jonathan W.; Shih, Terri; Alavi, Afsaneh; Hsiao, Jennifer L.; Shi, Vivian Y.
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic inflammatory dermatosis with recurrent painful nodules and abscesses affecting the intertriginous areas. Patients often experience a significant negative impact on quality of life from associated pain, discharge, odor, scarring, and social stigma. Even with complex medical regimens, patients may report inadequate disease control. Lifestyle changes and complementary and alternative medicines (CAM) are used by a majority of HS patients. Conventional medicines and lifestyle and CAM modalities strategically incorporated together can increase treatment satisfaction and success. Objective: We aim to highlight lifestyle and CAM treatment modalities to use alongside conventional treatment plans for HS patients. Findings: Lifestyle modifications for HS patients include weight loss, reducing skin friction, smoking cessation, and stress reduction. Dietary modifications for HS patients include limiting foods containing dairy, Brewer's yeast, and simple carbohydrates, appropriate caloric reduction, and consuming foods in the Mediterranean diet. The CAM modalities studied in HS are vitamin D, niacinamide, vitamin B12, zinc, and magnesium. Potential CAM modalities for HS include probiotics, cannabinoids, turmeric, bathing regimens, and acupuncture. Conclusion: This review is a guide for clinicians to provide evidence‐based care for HS patients seeking non‐pharmacologic treatment modalities such as weight loss, clothing choices, dietary changes, and use of supplements and complementary medicine. Lifestyle and CAM modalities may be used in parallel with conventional medicines to synergistically improve patient disease outcomes.